Feasibility of submaterial module for reproductive system disorders based on inventory of medical plants - K. Khairunnisa; Ruqiah Ganda Putri Panjaitan; T. Titin; Zhang Jia (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Modules are teaching materials designed to be studied by students independently or with minimal guidance from educators because they are equipped with their learning instructions. This study aims to determine the feasibility of teaching materials for reproductive system disorders submaterial modules from the inventory of medicinal plants that facilitate and relieve menstrual pain in Tumiang Village, Samalantan District, Bengkayang Regency. The research method was used research and development (R&D) Borg and Gall model, including potential problems, data collection, product design, design validation, and product revision. The validation of the teaching materials was done by five validators using validation sheets. The aspects assessed in the validation sheet consist of content, language, presentation, and graphics. The validation data were analyzed using the Content Validity Ratio (CVR) and the Content Validity Index (CVI). The results of the validation of the module’s instructional materials yielded a CVR value of 1.00 for each criterion with a valid category and a CVI value of 1.00 with a valid category. Based on these results, it can be concluded that the module on reproductive system disorders from the results of the inventory of medicinal plants that facilitate and relieve menstrual pain is suitable for use as teaching material.